Dexmedetomidine decreases cerebral hyperperfusion syndrome incidence following mechanical thrombectomy in acute ischemic stroke: a double-blind, randomized controlled trial - Gao, Ziwen; Zhou, Rihua; Sang, Benling; Gao, Guolin; Li, Shu; Li, Jiaxin (Frontiers in Neurology, 2025)
BackgroundCerebral hyperperfusion syndrome (CHS) is a serious complication that can follow intravascular mechanical thrombectomy for acute ischemic stroke (AIS). Dexmedetomidine (Dex), a selective α₂-adrenoceptor agonist used as a sedative, has known neuroprotective effects in ischemic cerebral injury. This double-blind, randomized, placebo-controlled clinical trial (ChiCTR 2500105088) aimed to evaluate the preventive impact of low-dose Dex on CHS after AIS.MethodsPatients with AIS and anterior circulation occlusion scheduled for endovascular mechanical thrombectomy from August 2023 to October 2024 were included. The occluded vessels were the internal carotid artery intracranial portion, M1, or M2 segments of the middle cerebral artery. After obtaining informed consent, patients were randomly allocated to two groups: one group (n = 70) received intravenous Dex with a 10-min preoperative loading dose of 0.5 μg/kg, followed by postoperative maintenance infusion at 0.1 μg/kg/h until 72 h postoperatively. The other group (n = 71) received an equal volume of placebo (normal saline) via the same intravenous route and schedule. The principal outcome was the occurrence of CHS evaluated through the seventh day post-operation. Subsidiary outcomes comprised the National Institutes of Health Stroke Scale (NIHSS) score within 24 h post-operation, Modified Rankin Scale (mRS) scores at discharge, within 30 days and 90 days post-operation, the duration of ICU stay, total hospital stay length, and the 30-day all-cause mortality rate.ResultsA statistically significant reduction in the occurrence of CHS was observed in the Dex group relative to the placebo group: among 70 patients in the Dex group, only 2 cases of CHS were identified (2.9%), whereas 10 cases occurred in the placebo group (14.1%) from a total of 71 patients. This difference was confirmed by both odds ratio (OR: 0.203; 95% confidence interval [CI]: 0.046–0.893; p = 0.017) and hazard ratio (HR: 0.194; 95% CI: 0.043–0.887; p = 0.018) analyses. Additionally, the Dex group showed significantly lower postoperative pain scores assessed via the Numeric Rating Scale (NRS) on postoperative day 1 and day 3 compared with the placebo group (p < 0.0001).ConclusionDex significantly reduced 7-day CHS occurrence after mechanical thrombectomy in AIS patients and lowered postoperative pain scores.Clinical trial registrationwww.chictr.org.cn, identifier ChiCTR 2500105088.